SILICA SPECIATION IN AQUEOUS FLUIDS AT HIGH PRESSURES AND HIGH TEMPERATURES - Zotov N.; Keppler H. (My University, 2002)
In-situ Raman measurements of silica speciation in aqueous fluids in equilibrium with solid quartz are reported to 14 kbar and 900 °C. Silica speciation in the fluid depends strongly on temperature and pressure. The Raman spectra indicate that below 600 °C and 6-8 kbar, only H4SiO4 monomers are present, while H4SiO4 monomers and H6Si2O7 dimers coexist at higher temperatures and pressures. Above temperatures of about 850-900 °C and pressures of 12-13 kbar higher polymers may be present in significant concentrations. The enthalpy of the polymerization reaction 2H4SiO4#H6Si2O7+H2O at 5 kbar pressure is ΔH=12.6+/-1.3 kJ/mol, while the reaction entropy is ΔS=40.7+/-1.3 J/mol K. The change of the molar volume of the solute ΔVsol=VH6Si2O7-2VH4SiO4 is virtually constant over the pressure and temperature range studied and equal to -39+/-14 cm3/mol.
Keywords: SILICA SPECIATION; AQUEOUS FLUIDS; DIAMOND-ANVIL CELL; SOLUBILITY; RAMAN SPECTROSCOPY; HIGH PRESSURE